Urgensi Kebersihan Gigi dan Mulut sebagai Implementasi Thaharah Menurut Pandangan Aswaja - Nining Handayani; Hilda Santosa; Selly Maulidina; Faiz Karim Fatkhullah (Journal of Innovative and Creativity, 2026)
Oral and dental health is frequently neglected in global public health priorities despite its profound impact on quality of life and socioeconomic burdens. This research aims to analyze the urgency of oral hygiene as an implementation of Thaharah within the Ahlussunnah wal Jamaah (Aswaja) framework, integrating theological and scientific perspectives. Employing a narrative review methodology, this study synthesizes classical Shafi'i jurisprudence and Al-Ghazali’s Sufism with contemporary biomedical data (2014-2025) sourced from Scopus and PubMed databases. The findings indicate that within the Aswaja tradition, oral hygiene transcends secular routines, functioning as a religious obligation with spiritual and metaphysical dimensions, including the sensitivity of angels to halitosis. Scientifically, the use of miswak (Salvadora persica) is validated through bioactive compounds such as benzyl isothiocyanate, fluoride, and silica, which exhibit potent antimicrobial properties and enamel protection. This integration reframes oral hygiene within the Maqasid Syariah (Objectives of Islamic Law), specifically Hifz al-Nafs (preservation of life/health) and Hifz al-Din (preservation of religion). The study concludes that evidence-based Islamic oral hygiene practices provide a holistic foundation for systemic health and the enhancement of religious devotion.